Effectiveness of micro-nanobubble aeration and phytoremediation in treating filtered palm oil mill effluent on bacteria diversity and water properties - RIA KARNO; ENDANG ARISOESILANINGSIH; IRFAN MUSTAFA; DIAN SISWANTO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Karno R, Arisoesilaningsih E, Mustafa I, Siswanto D. 2024. Effectiveness of micro-nanobubble aeration and phytoremediation in treating filtered palm oil mill effluent on bacteria diversity and water properties. Biodiversitas 25: 4340-4349. Palm oil waste treatment has gained much significance in recent years, as the palm oil industry has been on the rise. In addition, the biological removal of open treatment ponds and the subsequent activity of microorganisms, mainly bacteria, have been given special consideration. Therefore, this study aimed to evaluate the effectiveness of phytoremediation (Phyt) and micro-nanobubble (MnB) aeration technologies on the improvement of physicochemical properties of filtered palm oil mill secondary effluent (POMSE). The effect of the technologies on bacteria density and composition using a laboratory-scale reactor with 24-hour incubation was also explored. Metagenomic analysis using Next Generation Sequencing (NGS) and traditional methods, such as Total Plate Count (TPC) was used to evaluate bacteria density and composition. Physicochemical analyses were then conducted using an Indonesian standard method (SNI). The results showed that the MnB+Phyt reactor was more effective in reducing waste pollutants and meeting waste standards than control, MnB, or Phyt reactors after 24 hours. In addition, TPC counts showed that the highest bacteria density occurred at the 6-hour mark in the MnB+Phyt, Phyt, or MnB reactors compared to the control. Despite variations in bacteria composition among reactors, the dominant phylum and family were Pseudomonadota, Comamonadaceae, Zoogloeaceae, and Alcaligenaceae. The results also showed that MnB treatment significantly increased alpha diversity and altered genera composition. In conclusion, MnB aeration and phytoremediation technologies effectively reduced filtered POMSE pollutants with a removal percentage ranging from 28.37% to 56.69% under 24-hour treatment.